Interactive Shielded Metal Arc Welding Technique E-Module for Vocational High Schools - Setuju; Erix Satria Yoga; Sigit Purnomo (Journal of Education Technology, 2025)
Learning Shielded Metal Arc Welding techniques in vocational high schools still faces various challenges, including students’ low level of understanding, high rates of practical errors, and the limitations of conventional learning media that are static and lack interactivity. This study aims to develop and examine the feasibility of a Shielded Metal Arc Welding Technique E-Module as an interactive learning medium to improve students’ understanding and learning outcomes. The study employed a Research and Development (R&D) method using the Four-D model (Define, Design, Develop, and Disseminate). The research subjects consisted of one subject-matter expert, one media expert, and 29 tenth-grade vocational high school students. Data were collected through observations and questionnaires and then analyzed using descriptive statistics with a Likert scale. The validation results showed that the E-Module obtained a feasibility score of 89% from the subject-matter expert and 90% from the media expert, both categorized as very feasible. Student responses indicated a feasibility level of 93%, suggesting that the E-Module is easy to use and engaging. The effectiveness test using a pretest–posttest design revealed an increase in the average score from 65 to 85, with 85% of students exceeding the Minimum Mastery Criteria and a 35% reduction in practical errors. In conclusion, the interactive Shielded Metal Arc Welding Technique E-Module is considered highly feasible and effective, and it is capable of enhancing students’ motivation, learning independence, and learning outcomes in welding instruction.